Combining Clientelism and Incumbency Advantage: Political Strategy in Candidate Selection for the 2017 Local Head Election in Bekasi Regency - Paskarina, Caroline; Hermawati, Rina; Yunita, Desi (Jurnal Politik Indonesia: Indonesian Political Science Review, 2019)
This article discusses the post-clientelist initiatives used by political parties in the selection of candidates within the party to determine the regent and vice regents nominated for the local election. Candidate selection is the political domain of political parties, but in the context of figure-based politics, parties tend to play more as political vehicle in the candidacy of local head. Through this role, resource exchanges take place between parties and candidates within the internal party candidacy arena. Using qualitative methods through in-depth interviews and observations of candidate selection in the Bekasi Regent 2017 election, this article seeks to reveal how post-clientelist initiatives are used by party elites to optimize the incumbency advantage as main political resource in the candidate selection to determine who will pair the incumbent. The results show that the dominance of party elites in candidate selection process determines how financial resources and political support are optimized to win the incumbent. Decision to choose the vice-regent from the same party while still forming coalitions with other parties indicates that post-clientelistic strategy is operated both internally and externally. This practice confirms the tendency of the candidate selection model to be more inclusive because it involves other parties, but remains pragmatic.